Decreased PON1 activity as a biological marker for depressive disorders: a narrative review - Oleg A. Levada; Oleksandra S. Troian (Journal of Affective Disorders Reports, 2025)
Background: This study conducts a narrative review to summarize evidence regarding changes in serum/plasma paraoxonase 1 (PON1) activity in patients with major depressive disorder (MDD) or other depressive disorders and assess their possible marker value. Methods: We searched the PubMed database for articles published from inception to December 2024 on the relationship between depression and PON1 activities/concentrations. Results: Seventeen articles from 2006 to 2022 were included in the final analysis. 70 % of the studies demonstrated a decline in PON1 (predominantly arylesterase activity) during MDD episodes and depressive disorders induced by methamphetamine and Parkinson`s disease. Lower PON1 paraoxonase activity was associated with the number of previous depressive episodes (DE), worse outcomes, and higher DE severity. Two studies showed an increase in PON1 activity after antidepressant treatment. The decline of PON1 has a genetic predisposition. QQ and QR genotypes of PON1 increased the odds of depression. MDD patients with QQ genotype (in contrast to QR and RR) showed lowered PON1 activity. Conclusion: There is a decline in arylesterase/paraoxonase activity and PON1 concentrations in MDD and secondary depressive disorders. The decline is also associated with the severity and number of DE. Antidepressant treatment might increase PON1 activity. Genetic predisposition and epigenetic mechanisms that decrease PON1 activity might disrupt antioxidative mechanisms and lipid metabolism, which could be a part of complex pathogenesis and/or lead to comorbid somatic MDD pathology related to accelerated aging. PON1 activity and concentrations decline might be a marker for MDD and other DE, whereas PON1 increase – for treatment efficacy.